2012
DOI: 10.5513/jcea01/13.2.1038
|View full text |Cite
|
Sign up to set email alerts
|

Is Agrotourism Popular on the Internet?

Abstract: There is growing literature on the importance of the Internet, such as the growing importance of the agri/agrotourism role in the tourism industry, but with little inspection of the relationship in the context of word of mouth. The assumption is that online word of mouth makes the understanding of agrotourism more popular, so the aim of this paper is to examine whether the "popularity" of agrotourism has grown on the Internet during past years during which the Internet has recorded exceptional growth. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Whereas the study conducted by Timms (2006) [13] revealed that there was potential to stimulate local agricultural production. On the contrary, to these studies, the work done by Brscic (2006) [5] revealed that the agro-tourism activities had not significant influence on the increase of agricultural production within agro-tourism households. www.extensionjournal.com Agro-ecosystems are ecosystems composed of both abiotic and biotic elements that interact with each other and the surrounding environment.…”
Section: Resultsmentioning
confidence: 80%
“…Whereas the study conducted by Timms (2006) [13] revealed that there was potential to stimulate local agricultural production. On the contrary, to these studies, the work done by Brscic (2006) [5] revealed that the agro-tourism activities had not significant influence on the increase of agricultural production within agro-tourism households. www.extensionjournal.com Agro-ecosystems are ecosystems composed of both abiotic and biotic elements that interact with each other and the surrounding environment.…”
Section: Resultsmentioning
confidence: 80%
“…It will provide a feeling of comfort, acceptance for tourists. Some of the principles that must be carried out are acting as a good host and willing to help tourists, providing information about polite customs and manners, showing an attitude of respect and tolerance towards tourists, displaying smiles and good hospitality [20], [26]. Therefore, a good mapping was also created to provide a good information of all elements both to the community and visitors.…”
Section: Empowering Tourism Awareness Group Based On Sapta Pesona Con...mentioning
confidence: 99%
“…Information stored in one's own memory is an internal source of information. Brščić et al (2013) affirm, the Internet offers various opportunities for promotions and for those who sell and buy agrotourism products and it is important to "be in trend". The search process often encompasses a larger number of external sources of information, including recommendations from friends and family, specialized literature, consultations with professionals and the Internet as an increasingly common source (Ho et al, 2012).…”
Section: Introductionmentioning
confidence: 99%